Briefing and Building Information Modelling: Potential for integration. (June 2017) - Koutamanis, Alexander
The article brings together the subjects of briefing and Building Information Modelling. It considers the brief as information source for Building Information Modelling and Building Information Modelling as an environment for automating brief-related analysis and guidance. The approach is characterized by feedforward and feedback, incorporation of constraints from the brief in Building Information Modelling, connection of briefing goals to performance analysis and correlation of requirements in the brief to Building Information Modelling object properties and relations. To test the approach, 10 briefs are parsed into goals, constraints and requirements, which are then considered for integration in Building Information Modelling. As the majority of these items can become part of a model and subject to automated analyses, integration of briefing in Building Information Modelling is proposed as a viable option that can improve design and briefing performance but also signals significant changes to briefing.